Juridical Analysis Of Adultery Issues In Article 411 Of Law Number 1 Of 2023 On The Criminal Code - Hermalika, Yosi; Yusi, Suryani; Agustina, Sakinah (JURNAL HUKUM SEHASEN, 2025)
The title of this thesis is "Legal Analysis of the Problem of Adultery in Article 411 of Law No. 1 of 2023 concerning the Criminal Code"This study aims to explain the existence of human rights in Article 411 of Law Number 1 of 2023 concerning the Criminal Code concerning the crime of adultery from the perspective of human rights in Indonesia and human rights in Islam. The expansion of the meaning of adultery in Article 411 of the 2023 Criminal Code is considered to have adopted the concept of adultery from religious teachings, especially Islam, and raises human rights issues in the category of violations of a person's right to privacy. The regulation of adulterers who are not bound by marriage into the crime of adultery makes the state considered to have intervened far in the realm of the privacy of its citizens. This study uses a type of juridical-normative research and library research by conducting a study of laws and regulations, legal documents, books, and journals related to the title of this thesis. The results of the study show that the position of human rights in Indonesia is as a constitutional right. For this reason, every law and regulation must refer to the principle of humanity. Human rights can still be limited as long as the restrictions are regulated by law, including the formulation in Article 411 of the 2023 Criminal Code concerning Adultery which limits a person's personal relationships to maintain and protect the right to a sense of security, honor and good name of others. In addition, according to human rights in Islam, Article 411 of the 2023 Criminal Code has provided benefits and guaranteed the rights of the general public. With the existence of criminal penalties for perpetrators of adultery, both those who are married and those who are not married, it has provided the right to protection of honor and descendants as well as protection of children's rights in terms of inheritance.